Microstructure and oxidation resistance of Pd+Zr and Pd+Hf co-doped aluminide coatings deposited on Mar-M247 nickel superalloy - Romanowska, Jolanta; Zagula-Yavorska, Maryana (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Pd+Zr and Pd+Hf co-doped aluminide coatings were deposited on the nickel superalloy Mar-M247 by palladium electroplating followed by zirconization-aluminization or hafnization-aluminization processes. Both coatings consisted of two zones, the outer and the interdiffusion zone consisting of the β-(Ni,Pd)Al phase. Hafnium and zirconium formed inclusions deposited at the edge of the zones and near the surface (only in the Zr+Pd modified coating). The oxidation resistance of the aluminide coating co-doped with Pd+Zr was significantly better than the one co-doped with Pd+Hf. The hafnium content in the Pd+Hf co-doped coating could exceed the limit.